Association between social isolation, level of physical activity and sedentary behavior in pandemic times - David Michel de Oliveira; Luiz Fernando Gouvêa-; Verônica dos Santos da Costa; Edlaine Faria de Moura Villela; Eduardo Vignoto Fernandes (Universidade de Fortaleza, 2021)
Objective: To analyze the association between social isolation (SI), physical activity level (PAL) and sedentary behavior in the university community in pandemic times. Methods: A cross-sectional epidemiological study was carried out from May 7 to June 4, 2020, with 194 participants linked to the Federal University of Jataí (Universidade Federal de Jataí - UFJ), in Goiás, Brazil. Data were collected using a form created on Google Forms® and sent to the email addresses of the academic community of UFJ to assess socioeconomic characteristics, lifestyle, body composition, physical activity level, and sedentary behavior, taking into account the periods prior to and during SI. Data were analyzed using descriptive and inferential statistics, with p<0.05 considered significant. Results: The study participants were predominantly women (n=141; 72.6%), 18-27 years old (n=100; 71%), single (n=96; 68%), students (n=110; 78%), and had no pre-existing diseases (n=94; 67%). Increases in the body mass and body mass index (BMI) (p<0.05) were observed during SI, and physical activity downtime increased for all participants, regardless of sex (p<0.05). Conclusion: SI recommended by health managers due to the pandemic caused by COVID-19 was responsible for inducing an increase in body mass and BMI accompanied by an increase in screen time during the week, as well as a decrease in the PAL of individuals belonging to the community of university students of UFJ.